The Role of Inclusive Education in Providing The Activity of Students with Disabilities (Web of Teachers: Inderscience Research, 2023)
The article covers the issues of organizing inclusive education in the conditions of the innovative cluster of pedagogical education, creating the necessary conditions for children with disabilities in a general educational institution, preventing discriminatory problems, and determining the social and psychological environment.